2022
DOI: 10.1101/2022.09.13.22279818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma phosphorylated tau 181 predicts amyloid status and conversion to dementia stage dependent on renal function

Abstract: BackgroundPlasma P-tau181 is associated with tau and amyloid pathology in Alzheimer’s disease (AD). Its use as a biomarker for the detection of AD (along the disease continuum, from preclinical to mild cognitive impairment (MCI) and dementia) is increasingly established, as is its prognostic value. Further validation in different settings of use is still needed, as well as investigation of confounding factors that might indirectly influence its blood concentration.MethodsThis study is ancillary to the prospect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…To this end, here, we present three papers that illuminate the practical application of blood biomarkers—Altomare et al 7 (Geneva Cohort) and Lehman et al 8 (BALTAZAR cohort) assess the performance of AD blood biomarkers in memory clinics, and Veria et al 9 highlight potential for positive AD blood biomarkers in amyotrophic sclerosis.…”
mentioning
confidence: 99%
“…To this end, here, we present three papers that illuminate the practical application of blood biomarkers—Altomare et al 7 (Geneva Cohort) and Lehman et al 8 (BALTAZAR cohort) assess the performance of AD blood biomarkers in memory clinics, and Veria et al 9 highlight potential for positive AD blood biomarkers in amyotrophic sclerosis.…”
mentioning
confidence: 99%
“…Other parameters such as age or BMI can also confound the value of AD prognostic biomarkers. For pTau181, we previously found impaired renal function likely undermines diagnostic performance 32 . In the same cohort, we now study pTau217 and we observed that renal function and other potential confounding factors have a minimal effect on its performance.…”
Section: Discussionmentioning
confidence: 99%
“…These results further emphasize the importance of standardizing assays and procedures for plasma biomarkers in future research and clinical settings. Moreover, plasma biomarker levels and their diagnostic accuracy appear to be affected by multiple comorbidities 41,42 and peripherally derived plasma biomarkers 43,44 . Therefore, comprehending the impact of these comorbidities on plasma levels is also crucial for their prospective interpretation in the context of clinical screening, diagnosis, or prognosis at the population level.…”
Section: Discussionmentioning
confidence: 99%